JURNAL ILMU KESEHATAN JURNAL ILMU KESEHATAN STIKES DUTA GAMA KLATEN - maryanti S.SiT.,M.Kes (STIKES DUTAGAMA KLATEN, 2022)
Background: Perineal rupture is a tear that occurs in the perineum during labour. The highest cause of maternal death is bleeding, one of the causes of which is perineal rupture with an incidence rate of 16%.Research Objectives: To analyze the factors that influence the incidence of perineal rupture in women giving birth based on previous studies.Research Methods: This study used the Scoping Review method with various references, research journal searches were conducted from several databases such as Google Scholar, Science Direct and Pubmed with related keywords, such as